Aplicativo web para pedidos on-line de productos alfareros en el GAD la Victoria - Latacunga Cuchiparte, Wilson Geovanny (2021)
The present work is based on the development of a web application for on-line orders of pottery products in the GAD La Victoria, the orders were originally handled manually in notebooks, booklets without any type of support; The objective of this application is to automate each activity through the web, the client will be able to manage their order in a safe and reliable way complying with the necessary protocols, an analysis work was carried out with the president Mr. Diego Bolívar Espinoza and potters who contributed with the entire knowledge base, survey of requirements, needs that were observed in the Institution. The planned objective has been met; the web application fully meets the expectations of the GAD, which has undergone a rigorous validation process, has the guarantee and implementation endorsement granted by the end user who will be in charge of manipulating and managing any change